2012
DOI: 10.1002/adhm.201200205
|View full text |Cite
|
Sign up to set email alerts
|

Biomimetic Calcium Carbonate Concentric Microgrooves with Tunable Widths for Promoting MC3T3‐E1 Cell Functions

Abstract: Biomimetic, self-assembled calcium carbonate (CaCO(3) ) concentric microgrooves with groove widths of 5.0 and 10 μm were fabricated through simply controlling incubation temperature. Mouse pre-osteoblastic MC3T3-E1 cells were cultured on flat and microgrooved substrates of CaCO(3) and their adhesion, spreading, proliferation, alkaline phosphatase activity, and calcium content were remarkably enhanced by the microgrooves, in particular, the narrower ones. Furthermore, focal adhesions and actin filaments of MC3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 49 publications
(70 reference statements)
1
26
0
Order By: Relevance
“…[30][31][32] Many studies have investigated the interaction of osteoblasts with porous Ta, Ta discs, and Ta coatings, but limited research has been performed on the interaction of osteoblasts with Ta-NPs. Ninomiya et al 14 compared the effects of various implant surfaces (Ti mesh, cobalt-chromium beads, and porous Ta) on osteoblast proliferation and found that the osteoblast proliferation on porous Ta was significantly greater than that on the other surfaces, thus revealing porous Ta as a superior scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…[30][31][32] Many studies have investigated the interaction of osteoblasts with porous Ta, Ta discs, and Ta coatings, but limited research has been performed on the interaction of osteoblasts with Ta-NPs. Ninomiya et al 14 compared the effects of various implant surfaces (Ti mesh, cobalt-chromium beads, and porous Ta) on osteoblast proliferation and found that the osteoblast proliferation on porous Ta was significantly greater than that on the other surfaces, thus revealing porous Ta as a superior scaffold.…”
Section: Discussionmentioning
confidence: 99%
“…[34][35][36][37][38][39] In this study, the ALP activity of MG63 cells on the VH/rhBMP-2/n-MZS exhibited significantly higher levels of expression than that on the VH/rhBMP-2/MZS system at 7 days, indicating that the cells differentiated more quickly …”
Section: Alp Activitymentioning
confidence: 55%
“…30 The transition from newly formed bone to a mature one is a gradual process where there is a dynamic interaction between scaffolds and the invasion of bone cells/tissues. [31][32][33] In this study, it was found that new bone tissues gradually increased and the materials continued to reduce for both l-MBPC and l-BPC scaffolds after implanting at different time points. At 3 months, a large quantity of new bone tissues formed in l-MBPC scaffolds, which was significantly higher than in l-BPC scaffolds.…”
mentioning
confidence: 59%